Congenital Absence of the Oval Window: Radiologic Diagnosis and Associated Anomalies - Zeifer, Barbara; Sabini, Paul; Sonne, Jonathan (American Journal of Neuroradiology, 2000)
BACKGROUND AND PURPOSE: In most children with conductive hearing loss, acquired otitis media and/or middle ear effusion are ultimately diagnosed. Congenital conductive hearing loss is a rare condition; absence of the oval window is an unusual pathogenesis for this type of hearing impairment and can be associated with an anomalous horizontal facial nerve canal. Our goal was to describe the imaging features of congenital absence of the oval window, to determine the frequency with which anomalous development of the horizontal facial nerve canal occurs, and to review the developmental error responsible for this malformation.METHODS: Nine temporal bones in seven patients (5 to 36 years old) were found to have an inadequately formed oval window on high-resolution CT scans; seven ears showed complete lack of oval window formation, and two showed partial absence of the oval window. Records were reviewed for clinical information, and images were examined for associated anomalies.RESULTS: Six of nine ears with abnormal oval window formation showed malposition of the horizontal facial nerve canal. In each of these, the canal was abnormally low, overlying the expected location of the oval window; three of the canals lacked a visible bony covering. Seven of the nine ears were found to have a dysplastic or absent stapes.CONCLUSION: Congenital absence of the oval window can be diagnosed on CT studies. In the present series, this anomaly was associated with a grossly aberrant horizontal facial nerve canal in six of nine involved ears. Familiarity with the developmental sequence of oval window formation fosters an understanding of these anomalies. Preoperative recognition is important clinically, as a low facial nerve will block surgical access to the oval window and its presence will alter patient management.